Jurnal Penyuluhan: Tingkat Kinerja Penyuluh Pertanian di Kabupaten Konawe Provinsi Sulawesi Tenggara - Syafruddin Syafruddin, Sunarru Samsi Hariadi, Sri Peni Wastutiningsih (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
This study aims to provide information on the level of performance of agricultural extension Konawe Southeast Sulawesi and the factors that influence. The unit of analysis This study is of agricultural extension, taken/withdrawn in census namely throughout civil servants of agriculture extension worker of the research sites (130 people), while of the objectivity to assess the performance of agricultural extension also taken two farmers who are in the target area so that the number of agricultural extension farmers is 260 people.